Adeeb of Dr Taha Hussein, Translated by Professor Munawar Hussain: An Analysis - Riaz Ahmad (بازیافت)
The famous Novel Adeeb is written by a blind Egyptian modern Arabic wri ter Dr. Taha Hussain and Translated in Urdu by Prof. Muhammad Munawwar. He is renowned for his urdu translation of Arabic, English and Persian.His translation style is very creative and comprehenive. Taha Hussain's this Novel is the portrayal of an author whose idiosyncrasies make him a unique character. Inspite of being a blind man, he possesses phenomenal foresight. Craving for a Paris-based fellowship in literature, he divroces his wife. But after some time, formented by regrets, he languishes in his sense of guilt. This novel denotes Taha Hussain's attitude to life.